2010
DOI: 10.21608/jfds.2010.82107
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Chemical and Nutritional Quality During Cold Storage of Some Fruit and Vegetable Juice Blends.

Abstract: Fresh juice blends are a popular food daily consumed by all people with different age and standard living for their low prices and pleasant flavor. In spite of the cheap price of these juices; they have high nutritive value for their high content of βcarotene, minerals as calcium, potassium, magnesium and iron. So, the main target of such manuscript was to follow up main components changes in untraditional fruit and vegetable juice blends during cold storage (5-7°C) for three months. Obtained results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…The results revealed a slight decrease in pH value (from 6.00–6.28 to 4.89–5.29) with an increase in the titratable acidity (TA) (from 0.12–0.14 to 0.23–0.27% malic acid/100 g) of date samples with longer storage time ( Table 2 ). Tabikha et al [ 37 ] attributed the decrease in the pH of fruits and vegetables during storage to the conversion of sugars to alcohols and acids through the activity of some microorganisms. In addition, Mohammed et al [ 38 ] reported that the pH of date fruits decreases due to natural changes that occur with the progress of maturity stages, where pH reaches the lowest value in the final stage of ripening.…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed a slight decrease in pH value (from 6.00–6.28 to 4.89–5.29) with an increase in the titratable acidity (TA) (from 0.12–0.14 to 0.23–0.27% malic acid/100 g) of date samples with longer storage time ( Table 2 ). Tabikha et al [ 37 ] attributed the decrease in the pH of fruits and vegetables during storage to the conversion of sugars to alcohols and acids through the activity of some microorganisms. In addition, Mohammed et al [ 38 ] reported that the pH of date fruits decreases due to natural changes that occur with the progress of maturity stages, where pH reaches the lowest value in the final stage of ripening.…”
Section: Resultsmentioning
confidence: 99%
“…The results in Table 2 exhibited a decrease in the pH values (from 6.07-6.25 to 4.93-5.21) with a concomitant increase in TA (from 0.13-0.15 to 0.24-0.28%) with extended storage. Tabikha et al [34] illustrated the decrease in the pH of stored fruits with the metabolic activity of microorganisms that can convert some sugars into alcohols and acids. Additionally, the decrease in the pH values of the stored dates could be explained by the natural changes that occurred with the progression of the maturity process; that is, the pH can reach its lowest value in the ripening stage [35].…”
Section: Physicochemical Qualitiesmentioning
confidence: 99%